A textual analysis of examiners’ feedback on the literature review in Indonesian doctoral candidates’ dissertation reports - Lubis, Arif Husein; Damayanti, Ika Lestari; Sukarya Soetedja, Zakarias; Hutasuhut, Mahmud Layan (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
Doctoral candidates’ ability to elaborate ideas and advance disciplinary scholarships is crucial in constructing well-grounded and comprehensive dissertation reports. To support the candidates, supervisors’ and examiners’ constructive feedback plays a pivotal role, as they are the gatekeepers of the quality of the dissertation reports. This paper reports on the investigation of two categories of feedback – content-focused and form-focused feedback examiners provided for several doctoral candidates’ literature review section in their dissertation reports at an Indonesian university. Nine review results from the fields of language and arts were collected and qualitatively analysed. A synthesized rubrics was used to analyse the excerpts of both feedback categories. The analysis results revealed that the examiners’ content-focused feedback emphasized the analytical aspect and relevance of a literature review. This was justified by the examiners’ suggestions to present an in-depth and wide discussion of the research variables and to highlight the contribution of the research to the advancement of knowledge in the field of study. In addition, their form-focused feedback highlighted the clarity of expressions and the mechanics in formulating the sentences. This paper ends with a proposal of developing the rubrics to capture the quality of the doctoral candidates’ literature review section more comprehensively.